A novel benzoxazine derived from diphenol amide for toughing commercial benzoxazine via copolymerization. Issue 19 (6th July 2022) - Zheng, Yanglei; Qian, Zizhao; Sun, Haoran; Jiang, Junyi; Fu, Feiya; Li, Haidong; Liu, Xiangdong
Abstract: Polybenzoxazines have a variety of advantages over most polymers, but the brittle feature limits the range of their applications. The most effective way for benzoxazine toughing is to copolymerize them with a well‐designed benzoxazine monomer able to contribute self‐plasticizing action. Here, a new bio‐based benzoxazine was synthesized from diphenolic acid (DPA), the sustainable candidate of bisphenol A. By introducing three aliphatic chains into DPA, the special benzoxazine able to provide remarkable toughness effect is obtained. For the synthesis, DPA is amidated using lauryl amine to diphenolic lauramide (DLA) first, then convert to a benzoxazine (DLA‐la) by Mannich‐like reaction with lauryl amine and paraformaldehyde. A commercial benzoxazine, bis(4‐(2H‐benzo[e][1, 3]oxazin‐3(4H)‐yl)phenyl)methane (PH‐ddm), is employed as the toughing object to test the possibility of using DLA‐la would offer a significant toughing effect. Experimental results show that DLA‐la/PH‐ddm blending would result in a perfect resin without phase separation, which exhibits an improved elongation at break higher by 70.5% than the bulk PH‐ddm resin, while keeps tensile strength at 44.69 MPa. As the proposed toughing principle could be applied to a variety of commercially available benzoxazines, this research broadly contributes toward the development of benzoxazine industries. Abstract :